33 - MOTIVATION FOR THE PRACTICE OF CYCLING (Fiep Bulletin - online, 2022)
Currently, there has been a growing number of cycling practitioners, in a way that stimulates and motivates more and more the practice and enjoyment of it, concluding that cycling is a fantastic sport, where the athlete is exclusively both the rider and the engine, in addition to being accessible to everyone, regardless of social class, gender or age. Cycling is an excellent physical activity and is strongly related to the quality of life level of the requirements and the environment where you live. Thinking about it, we did this research with the objective of identifying the motivational aspects for the Cycling practice. By contextual analysis, the study was carried out with 22 cycling practitioners, 70% male and 30% female. The values of bicycles stood out, relatively cheap as they fluctuated below four thousand reais (86.36%) and few above this value (13.64%). Some categories were identified, which stood out from the others, such as maintaining health, contact with nature and avoiding stress. It was clear that such reasons legitimize adherence to the sport since it was identified that the subjects’ practice without intentions of competition. Conclusion the main motivations for the practice of cycling as a physical activity and the pursuit and maintenance of health and the positive psychological effects that the sport offers are considered.